Profesionalisme Bisnis dalam Islam (UINSI Samarinda, 2014)
Islam commands work as worship to seek sustenance from God in order to meet their needs. Work to obtain sustenance halalan thayiban included in jihad fi sabilillah whose value is equal to implement the pillars of Islam. Working in the view of Islam is not just a work or work carelessly. But there are values that must be considered and practiced by every Muslim who works. These values is ihsan (good), jiddiyah (integrity), and itqan (professional). The professionalism of the Prophet Muhammad in business clung to his nature and the nature of his virtues which Siddiq, amanah, fathanah and istiqamah. Siddiq properties are trustworthy and honest. Fathonah nature is to be smart. The nature of amanah is to carry out the tasks assigned and tablig are capable of doing good communication and constancy is firm stance and not easily discouraged. Professionals equated with Itqan. Itqan means doing at the best possible quality. Work professionally (Itqan) means devoting the best minds, the best focus, the best coordination, the best spirit and the best raw materials that are expected to produce the best as well. The best quality we have to do in all aspects of life, including in business. Prophet has declared the importance of quality in the work and serve. Business is the process of selling the works, products and services. The quality of our work will determine the reciprocation of our business. For that build professional attitude in business is very important in order to get the best results.